Echocardiographic assessment of cardiac dysfunction in maintenance hemodialysis patients - Alam, Md Zahid; Hossain, Mohammad Zakir (Bangladesh Critical Care Journal, 2017)
Background and Objectives: The hemodialysis (HD) procedure may acutely induce regional left ventricular systolic dysfunction. This study evaluated the echocardiographic parameters in patients with End Stage Renal Disease (ESRD) on HD and to correlate those with clinical findings, more specifically to see whether there is any change in ejection fraction (EF) by developing new regional wall motion abnormality (RWMA) after hemodialysis, and to correlate these changes with the symptoms & hemodynamic condition of the patients. Methodology: This prospective observational study was carried on a total of 100 adult ambulant patients with end stage renal disease (ESRD) on maintenance hemodialysis in the department of Hemodialysis, BIRDEM General Hospital, Shahbag, Dhaka. Their echocardiogram was done 30 min before and after the hemodialysis. Result: It was revealed that majority of the patients were above 60 years (39%), and male to female ratio of about 3:2. The study subjects had diabetes mellitus (79%), hypertension (96%), dyslipidemia (42%), and family history of ischemic heart disease (24%). Chest pain and breathlessness were present in 31% and 42% subjects respectively before hemodialysis. Palpitation (23%), dizziness (19%), oedema (43%) and raised JVP (15%) were seen in the study subjects. Mean (±SD) serum creatinine level was 9.38 (±2.22) mg/dl and hemoglobin level was 9.0 (±1.08) g/dl. Ejection fraction (EF) before hemodialysis were ?55, 40-54 & 30-39 in 62%, 34% and 4% study subjects respectively and after hemodialysis it was ?55, 40-54 & 30-39 in 44%, 46% and 10% study subjects respectively. After HD, left ventricular failure (LVF) occurred in 32% subjects. HD-induced regional left ventricular systolic dysfunction occurred in total 36 patients (36%) and total 14 (14%) patients developed LVF 30 minutes after dialysis. Patients with hemodialysis-induced left ventricular systolic dysfunction were more in those who had worse predialysis EF. Blood pressure, heart rate, chest pain, palpitation, raised Jugular Venous Pressure (JVP) and edema did not differ significantly before and after hemodialysis. Simple regression analysis revealed that the hemodialysis procedure significantly (P<0.05) induce regional left ventricular systolic dysfunction. Conclusions: HD acutely induces regional wall motion abnormalities in a significant proportion of patients. It occurs within 30 min after hemodialysis and is not related to changes in blood pressure, heart rate, JVP and oedema. Bangladesh Crit Care J September 2017; 5(2): 97-100